Aplikasi Sistem Informasi Pengelolaan Arsip pada Unit Pelayanan Pajak dan Retribusi Daerah Palmerah Jakarta - Yuni Fitriani; Roida Pakpahan (Paradigma, 2018)
In an organization the role of information technology is indispensable, especially in terms of data processing in organizations in which one of them is the archival management system to support the smooth operations of an organization, to accelerate the process of work so that more effective and efficient as well as faciliate document management became more regular. Archives holds a very important role in the smooth running of an organization, that is as a source of information and as a source of memory for the organization. Management of archives of tax BPHTB in Unit Pelayanan Pajak dan Retribusi Daerah Palmerah Jakarta still apply the archive administration management system manual. Archives management of process taxes BPHTB still being recorded, by means or recorded into the book as a media archive storage tax so that if a book is lost or damaged will complicate an employee to do a search and examination return all BPHTB archive is needed at any time. To overcome these problems, then the author administrative officer in performing management of archive, could provide the needed information quickly, can improve the efficiency and effectiveness of the work process, as well as streamline the activities of the organization.Keywords : Application of Management Information System for Archives, Structured Programming